Genetic divergence in cowpea [Vigna unguiculata (L.) Walp.] for yield components parameters - U.V. Patel (Electronic Journal of Plant Breeding, 2017)
Thirty two cowpea [Vigna unguiculata (L.) Walp.] genotypes were evaluated for 12 quantitative characters to estimate the genetic diversity existing among them by using Mahalanobis D2 statistics. The genotypes were grouped into eight clusters. The cluster strength varied from single genotype (Clusters IV, V, VI, VII and VIII) to 12 genotypes (Cluster II). The maximum inter-cluster distance (D2 = 35.43) was observed between cluster-VI and VIII. Clusters II, III and I had maximum 100-seed weight, number of seeds per pod and seed yield respectively. Cluster VIII had the highest mean value for the characters viz., number of pod per plant, number of green pods per plant and green pod yield per hectare (kg/ha), while the cluster III had a lowest mean value for days to 50 per cent flowering. On the basis of inter cluster distances, cluster VIII was found to be more divergent. Therefore, it was concluded that the genotypes belonging to these cluster should be inter-crossed in order to generate more variability.